Використання методу ексергетичного аналізу для оцінки ефективності роботи енергоперетворювальних комплексів скловарного виробництва - Кошельнік, Олександр Вадимович; Долобовська, Ольга Вікторівна; Круглякова, Ольга Володимирівна (Донецький національний технічний університет, 2017)
Для аналізу роботи складних енерготехнологічних комплексів скловарного виробництва запропоновано застосування методів, що базуються на використанні термодинамічних функцій. Розглянуто схему утилізації теплоти димових газів скловарних печей з термосорбційним компресором та водневою турбоустановкою. Проведено розрахунково-теоретичне дослідження ефективності роботи даної схеми, знайдено основні параметри роботи схеми при різному рівні температур димових газів, представлені результати термодинамічного аналізу енергоперетворювального комплексу з використанням водню в якості робочого тіла.

Modern energy technology complexes of glass production, in addition to glass furnace itself, also include systems for utilization of thermal waste energy resources. When equipping the furnace with evaporative cooling systems, the utilization system is supplemented by energy technology equipment, where low-potential water steam of cooling systems is used as energy carrier. Further improvement of complex energy technology plants requires the development of newer and more multifunctional research methods. For example, the methods of thermodynamic research, which are based on exergy functions, can provide quite complete information about the efficiency of energy conversing processes in these complexes. Waste heat recovery schemes with cogeneration are the most effective for recuperative glass furnaces taking into account possibilities of fuel energy potential using. Hydrogen turbines applying is promising in such cogeneration schemes. The existing level of flue gas temperature after glass furnaces corresponds to the temperature level, which is necessary for the thermal sorption compressors operation. Compressors of this type provide the necessary hydrogen pressure before the turbine. A computational study of the efficiency of the waste heat recovery plant with a thermal sorption compressor and a hydrogen turbine is carried out. The flue gas temperature range at the compressor inlet over 250 – 450 °C is considered while flue gas temperature at the compressor outlet is assumed to be constant and equal to 120 °C. The operating data for hydrogen circuit at the nodal points of the cycle is obtained. According to the calculation results, hydrogen turbine unit power at a flue gas temperature of up to 300 ° C is nothing more than 60 kW. At the same time, the system perfection coefficient reaches its maximum at the minimum level of flue gas temperatures (250 °C) at the utilization system inlet. Thus, when considering the possibility of using of energy-converting complexes with hydrogen turbine plants for glass plants, an additional complex analysis of the results taking into account both economic and technical factors should be carried out. The optimal parameters of waste heat recovery plants are possible to find only considering a complex set of interrelated factors with regard to the type of equipment used and its performance indicators.
Using the method of exergy analysis to evaluation the efficiency of energy-conversion of glass production plants
Keywords: піч скловарна; енергоресурси вторинні; утилізація; ексергія; водень; компресор термосорбційний; турбіна воднева; ефективність; коефіцієнт досконалості; glass furnace; secondary power resources; recycling; exergy; hydrogen; thermal sorption compressor; hydrogen turbine; efficiency; coefficient of perfection